Students Errors in Solving Plane Geometry Problems Using E-Learning-based Diagnostic Tests - Mukhlis Hidayat; Tuti Zubaidah; Munira Ulfa; Elizar Elizar (Universitas Syiah Kuala, 2023)
During the Covid-19 pandemic, the implementation of online and shift learning systems has been identified as one factor contributing to learning loss in mathematics problem-solving skills specifically in plane geometry problems. The primary objective of this research was to investigate the different types of errors committed by junior high school students in Banda Aceh, Indonesia, in solving plane geometry problems using e-learning diagnostic tests. A descriptive qualitative approach was adopted, and 24 Year 8 students were selected as subjects. The data were collected through tests and interviews, and data analysis involved data reduction, data presentation, data verification, and drawing conclusions. The findings revealed that the percentage of students' errors in solving conceptual problems, principal problems, and verbal problems were 76.39%, 68.75%, and 75%, respectively. Subsequently, the results from the second test and interviews with six students showed that students encountered several conceptual errors, including errors in stating angle symbols, errors in identifying the type of shape provided, errors in deducing information regarding properties, perimeter, and area of plane geometry, lack of knowledge regarding the application of the appropriate plane geometry formula, and inability to solve problems using the correct procedure. Principal errors were related to algebraic operations, while verbal errors involved translating problems and improper application of concepts and principles. The understanding of the types of errors will help teachers detect errors made the students early.